Pengaruh Ketepatan Waktu, Daya Tanggap, Dan Ketelitian Terhadap Kepuasan Masyarakat Dalam Pengurusan Surat Keterangan Domisili Usaha Pada Kantor Camat Bengkong - Adnan Adnan; Cornelia Cornelia; Hendri Herman (Jurnal Sains Sosio Humaniora, 2022)
The purpose of this study is to find out :(1) To find out the influence of punctuality on community satisfaction in the bengkong subdistrict office. (2) To find out the effect of responsiveness to community satisfaction in the bengkong subdistrict office. (3) To find out the influence of accuracy on community satisfaction in the bengkong sub-district office. (4) To find out the influence of punctuality, responsiveness and accuracy Simultaneously Affect community satisfaction in the bengkong sub-district office. The dependent variable of this study is community satisfaction (Y). Independent variables include: timeliness (X1), responsiveness (X2), and accuracy (X3). The research method used is quantitative research method. The sampling technique uses the slovin method with a sample count of 83 people. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis techniques used to answer hypotheses are multiple regression, t test, F test, and R2. The results of this study show that : (1). There is an effect of timeliness on community satisfaction in the bengkong sub-district office as evidenced by the calculation value of 2,478 with a significant value of 0.000 < 0.05 and a regression coefficient of 0.023, (2). There is an influence of responsiveness to community satisfaction in the bengkong sub-district office as evidenced by the t-count value of 5,794 with a significant value of 0.000 < 0.05 and a regression coefficient of 0.392, (3). There is a thorough influence on community satisfaction in PT bengkong sub-district office as evidenced by the value of t count of 9,973 with a significant value of 0.000 < 0.05 and a regression coefficient of 0.584, and (4). There is an influence of punctuality (X1), responsiveness (X2), and accuracy (X3), simultaneously on community satisfaction in the bengkong subdistrict office. evidenced by the calculated F value of 58,027 with a significant value of 0.000 < 0.05.